BIOMATSEN 2021 Abstract Book - Oral, Ahmet Yavuz; Aksan, Onur Alp; Oral, Zehra Banu Bahşi; Kol, Seda; Aşkan, Vala Can; Ozbey, Sayit; Akdemir, B. Şölen; Kocaman, Fatmanur (Gebze Teknik Üniversitesi, 2021)
BIOMATSEN intends to be a global forum for researchers and engineers to present and discuss recent innovations and new techniques in Biomaterials and Biosensors. In addition to scientific seminars, a wide range of social programs including boat cruises and visits to historical places will be available. The Organizing Committee also encourages companies and institutions to showcase their modern products and equipment in the conference area.
Keywords: Material Production Technologies; Malzeme Üretim Teknolojileri